Essential oils, active ingredients in hair formulations - Siham BOULENOUAR (Journal de la Faculté de Médecine d'Oran)
Essential oils are widely used in the field of cosmetics due to their countless benefits. Though natural, these active ingredients are nevertheless not devoid of toxicity and their use requires sound knowledge. This article proposes a non-exhaustive overview of the beneficial action of different essential oils on hair disorders that have been tested in vitro and/or in vivo.